Cadar Dan Ruang Kontestasi Penafsiran Otoritatif - Afifah, Nurul (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2019)
Deparating from the emergence of the contestation over the use of veils in Indonesia, this study was aimed to explore the problematic (debate)of the use of the veil and how the contestation of interpretation authority from the circles works in it. This study employed a historical approach. The result of this study shows that: (1)the problematic(debate)of veil can be classification in three periods;(i)Classic-medieval period; a fikih expert vs a fikih expert; by monodiciplnier approach (textual)(ii)contemporer period; a islamic expertvsa a islamic expert; by the interdiciplinier approach vs monodiciplinier or textual vs contextual(iii) media period; general society. (2) the problematic (debate) raises two aspect:(i)discontuniuty aspect: a paradigm shifting in a periode between the each other period, (i)continuitas aspect: in spite of totality the problematic (debate) is dissareed paradigm, but the real of theproblematic (debate) is related with the same normative texts.